Piriformospora indica: Potential and Significance in Plant Stress Tolerance - Gill, Sarvajeet S.; Gill, Ritu; Trivedi, Dipesh K.; Anjum, Naser A.; Sharma, Krishna K.; Ansari, Mohammed W.; Ansari, Abid A.; Johri, Atul K.; Prasad, Ram; Pereira, Eduarda; Varma, Ajit; Tuteja, Narendra (Frontiers in Microbiology, 2016)
Owing to its exceptional ability to efficiently promote plant growth, protection and stress tolerance, a mycorrhiza like endophytic Agaricomycetes fungus Piriformospora indica has received a great attention over the last few decades. P. indica is an axenically cultiviable fungus and exhibits its versatility for colonizing/hosting a broad range of plant species through directly manipulating mainly plant hormone-signaling during the course of mutualism. P. indica-root colonization leads to a better plant performance in all respect including enhanced root proliferation by indole-3-acetic acid production which in turn results into better nutrient-acquisition and subsequently to improved crop growth and productivity. Additionally, P. indica can induce both local and systemic resistance to fungal and viral plant diseases through signal transduction. P. indica-mediated stimulation in antioxidant defense system components and expressing stress-related genes can confer crop/plant stress tolerance. Therefore, P. indica can biotize micropropagated plantlets and also help these plants overcome transplantation shock. Nevertheless, it can also be involved in a more complex symbiotic relationship, such as tripartite symbiosis and can enhance population dynamic of plant growth promoting rhizobacteria. In brief, P. indica can be utilized as a plant promoter, bio-fertilizer, bioprotector, bioregulator and biotization agent. The outcome of the recent literature appraised herein will help us to understand the physiological and molecular bases of mechanisms underlying P. indica-crop plant mutual relationship. Together, the discussion will be functional to comprehend the usefulness of crop plant-P indica association in both achieving new insights into crop protection/improvement as well as in sustainable agriculture production.